"A ti pa" avec l'antillectuel Léon Damas vers une France décoloniale? - Gyssels, Kathleen 1963- (Brill, 2023)
"The third man of negritude, Léon Damas, aligned himself with the Harlem Renaissance and surrealists to transmit his urgent message: à ti pas, little by little, France was undergoing its decolonial transformation. He claims to be the "Antillectual" who crosses the Lines of language, territory, color, class and gender. This essay presents Léon Damas in another light, operating a double reversal of perspective, first by affiliating him with the African American triangle (Richard Wright) and the Harlem Renaissance poets and novelists (Langston Hughes, Claude McKay). Second, Damas, Fanon's contemporary whose chapters of Black Skin, White Masks resonate in many poems, also registers as a minor surrealist, following in the footsteps of Guillaume Apollinaire and Ghérasim Luca. This new circumference shows the poet of Cayenne as a precursor on all lines. A poet who has remained off-screen, off-song, proves to be the radical decolonial militant who remained frustrated to see how slowly ("à ti pas") the Republic was changing. The present essay is intended to be "Plea for the Antillectual" (Sartre) through the figure of the poet who remained in the shadow of Léopold Senghor and Aimé Césaire. It also shows that the overseas remains a territory with variable geometry, the third department being eclipsed by Martinique in the theories of autochthony and manufacturing of the Antillean-Guyanese classics"--
Keywords: Damas, Léon-Gontran -- 1912-1978; Négritude; Damas, Léon-Gontran / 1912-1978 / Criticism and interpretation; Negritude (Literary movement); Damas, Léon-Gontran / 1912-1978; Criticism, interpretation, etc; Literary criticism